N-Acetyl Cysteine Ameliorates High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease and Intracellular Triglyceride Accumulation by Preserving Mitochondrial Function - Hang, Weijian; Shu, Hongyang; Wen, Zheng; Liu, Jinyan; Jin, Zhiyuan; Shi, Zeqi; Chen, Chen; Wang, Dao Wen (Frontiers in Pharmacology, 2021)
Abstract: Rational: Nonalcoholic fatty live disease (NAFLD) is a kind of metabolic diseases characterized by liver steatosis. Excessive reactive oxygen species (ROS) originated from dysfunctional mitochondria is the major pathophysiological contributor in the development of NAFLD, and is thought to be a promising therapeutic target. A few reports demonstrating the anti-oxidative treatments for NAFLD. Methods: Male C57 mice were fed on normal chow diet (ND) or high fat diet (HFD) for 8 weeks. PBS or NAC was gavaged to mice. LO2 human liver cell line treated with palmitic acid (PA) was applied as cellular model. Western blot, immunofluorescence, biochemistry assay and pathological staining were used to investigate the mechanism of suppressing lipid accumulation of NAC. Results: NAC treatment was able to prevent HFD-induced NAFLD, as evidenced by less hepatic triglyceride accumulation and lipid droplet formation compared with that of mice in HFD group. NAC could preserve mitochondrial function by inhibiting excessive mitophagy and promoting mitochondria biogenesis to prevent ROS production. NAC also activated Sirt1 and preserved its protein level, and subsequently promoted mitochondria biogenesis via deacetylating PGC1a. Conclusion: We demonstrated that NAC may be an effective drug to treat NAFLD, which was related to its anti-oxidative and mitochondrial protective effect.